Investigating Difficulties Faced by Lecturers in Teaching General English - Sam Hermansyah (Journal of English Education and Teaching, 2023)
This research aimed to investigate the challenges encountered by the lecturer in delivering English language instruction to non-native speakers at a privately-owned institution in Sidenreng Rappang. The methodology employed for this study was a qualitative case study. The study involved a single English lecturer who expressed willingness to undergo interviews and observations while facilitating teaching and learning activities. The data was collected through interviews and observation as the primary research instruments. Thematic analysis was employed to analyze the collected data. The findings of the thematic analysis indicate that English language instructors encounter challenges in the course of delivering their pedagogical duties: 1) The need for more student engagement in the learning process; 2) Inadequate implementation of pedagogical strategies; 3) Insufficient provision of academic support; 4) Delayed submission of student assignments. The inference can be drawn that the students encountered challenges in comprehending the subject matter presented by the teacher due to the predominant use of the English language. The diminished level of student engagement during the educational experience can be attributed to the hybrid learning process, which combines in-person and remote instruction.